2015
DOI: 10.21608/jbaar.2015.106032
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Marker Alternations in the Spleen of Experimentally Hyperthyroid and Hypothyroid Rat.

Abstract: Apoptosis plays a critical role in the development and homeostasis of multicellular organisms, especially those with high cell turnover such as the lymphoid system. The current study aimed to examined the effects of changes in thyroid hormones on apoptosis of spleen in male rats. 30 rats were equally divided into three groups (10 animals each). G 1 , control group in which animals did not received any treatment; G 2 , Hypothyroid group in which rats received 0.05% 6-n-propyl-2-thiouracil (PTU) in drinking wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Table (1) showed that serum T 3 and thyroitropin (TSH) levels were significantly decreased (p<.05) and increased (p<.05), respectively in hypothyroid mice (G3) as compared to control and costus groups (G1&G2). Meanwhile, serum T 3 and TSH levels showed significant increase and decrease, respectively in hyperthyroid mice (G4) as compared to control and costus groups (G1&2).…”
Section: Induction Of Hypothyroid and Hyperthyroid Micementioning
confidence: 99%
See 2 more Smart Citations
“…Table (1) showed that serum T 3 and thyroitropin (TSH) levels were significantly decreased (p<.05) and increased (p<.05), respectively in hypothyroid mice (G3) as compared to control and costus groups (G1&G2). Meanwhile, serum T 3 and TSH levels showed significant increase and decrease, respectively in hyperthyroid mice (G4) as compared to control and costus groups (G1&2).…”
Section: Induction Of Hypothyroid and Hyperthyroid Micementioning
confidence: 99%
“…On the other hand, treatment of mice with costus extract improved serum T 4 to be around normal levels (Table 1). As shown in Table (1), the cotreatment of both hypo-and hyperthyroid mice with costus extract modulates disturbed thyroid hormones toward normal levels of the control.…”
Section: Induction Of Hypothyroid and Hyperthyroid Micementioning
confidence: 99%
See 1 more Smart Citation